A Novel Regenerative Technique Combining Bone Morphogenetic Protein‐2 With Fibroblast Growth Factor‐2 for Circumferential Defects in Dog Incisors. Issue 9 (1st September 2016) - Saito, Emiko; Saito, Akira; Kato, Hiroshi; Shibukawa, Yoshihiro; Inoue, Satoshi; Yuge, Fumihiko; Nakajima, Toshinori; Takahashi, Tomomi; Kawanami, Masamitsu
Abstract : Background: Periodontal regeneration of incisors is necessary for esthetic recovery. A novel regenerative method combining bone morphogenetic protein (BMP)‐2 and fibroblast growth factor (FGF)‐2 was developed. The purpose of this study is to evaluate periodontal healing, including root coverage, in circumferential defects of incisors. Methods: Fifty incisors in five beagles were used. After circumferential defects were surgically created, each group, consisting of ten recipient sites, received: 1) a double layer with FGF‐2 (2 μg)/collagen as inner layer and BMP‐2 (4 μg)/collagen as outer layer (FB‐DL group); 2) collagen impregnated with both FGF‐2 (2 μg) and BMP‐2 (4 μg) (FB‐M group); 3) BMP‐2 (4 μg)/collagen (B group); 4) FGF‐2 (4 μg)/collagen (F group); or 5) collagen (C group). Dogs were sacrificed 8 weeks post‐surgery, and healing was evaluated histologically. Results: The three groups treated with BMP‐2 showed enhanced new bone formation compared with control and F groups ( P < 0.05). Furthermore, connective tissue attachment with cementum regeneration in the FB‐DL group was significantly greater than in FB‐M and B groups ( P <0.05). Ankylosis in the FB‐DL group was significantly less than in FB‐M and B groups ( P <0.05). Gingival recession was inhibited significantly better in FB‐DL and FB‐M groups compared with control and B groups. Conclusion: These data support development of a double‐layer method combining BMP‐2 and FGF‐2 as a therapeutic approach to periodontal regeneration at incisors with horizontal circumferential defects.